Genome-wide analysis of DWD proteins in soybean (Glycine max): Significance of Gm08DWD and GmMYB176 interaction in isoflavonoid biosynthesis. - Shaomin Bian; Xuyan Li; Hemanta Mainali; Ling Chen; Sangeeta Dhaubhadel (PLoS ONE)
A subset of WD40 proteins with DWD motif has been proposed to serve as substrate receptor of DDB-CUL4-ROC1 complex, thereby getting involved in protein degradation via ubiquitination pathway. Here, we identified a total of 161 potential DWD proteins in soybean (Glycine max) by searching DWD motif against the genome-wide WD40 repeats, and classified them into 20 groups on the basis of their functional domains and annotations. These putative DWD genes in soybean displayed tissue-specific expression patterns, and their genome localization and analysis of evolutionary relationship identified 48 duplicated gene pairs within 161 GmDWDs. Among the 161 soybean DWD proteins, Gm08DWD was previously found to interact with an isoflavonoid regulator, GmMYB176. Therefore, Gm08DWD and its homologue Gm05DWD were further investigated. Expression profile of both genes in different soybean tissues revealed that Gm08DWD was expressed higher in embryo, while Gm05DWD exhibited maximum transcript accumulation in leaf. Our protein-protein interaction studies demonstrated that Gm08DWD interacts with GmMYB176. Although Gm08DWD was localized both in nucleus and cytoplasm, the resulting complex of Gm08DWD and GmMYB176 was mainly observed in the nucleus. This finding is consistent with the functional localization of CUL4-E3 ligase complex. In conclusion, the survey on soybean potential DWD protein is useful reference for the further functional investigation of their DDB1-binding ability. Based on the functional investigation of Gm08DWD, we speculate that protein-protein interaction between Gm08DWD and GmMYB176 may lead to the degradation of GmMYB176 through CUL4-DDB1complex.